Back plate and wedge use and individual ventral and dorsal swimming start performance: a systematic review - de Jesus, K.; de Jesus, K.; Fernandes, R. J.; Vilas-Boas, J. P. (Sports Biomechanics, 2022)
Individual starts for ventral and dorsal swimming events have changed. After the introduction of back plate and wedge, some studies (mainly on ventral starts) have aimed to clarify their benefits and optimal application. This systematic review is aimed at a critical appraise of the literature on the main findings for back plate and wedge usage. We explored the databases of PubMed, Scopus and Web of Science and conducted a manual search on the reference list of papers. We based our search on the quality scale of the National Health Institutes and found 25 studies that met the eligibility criteria and that scored 7.75 ± 1.18 and 8.0 ± 0.71 on fair-quality studies addressing kick and backstroke starts. Kick start has shown faster start time comparing with grab and track starts by reducing block time and increasing horizontal take-off velocity. Backstroke start using the wedge improved performance through a greater centre of mass vertical position at take-off, horizontal and vertical position at entry and underwater velocity. Swimmers have adopted technical variants of kick and backstroke start by changing block set-up and stance, which should be monitored considering anthropometrics and strength abilities.